Association of Trimethylamine N-Oxide Levels and Calcification in Culprit Lesion Segments in Patients With ST-Segment–Elevation Myocardial Infarction Evaluated by Optical Coherence Tomography - Li, Jiannan; Tan, Yu; Zhou, Peng; Liu, Chen; Zhao, Hanjun; Song, Li; Zhou, Jinying; Chen, Runzhen; Wang, Ying; Zhao, Xiaoxiao; Chen, Yi; Yan, Hongbing (Frontiers in Cardiovascular Medicine, 2021)
The presence of calcified plaques is one of the pathological phenotypes of acute coronary syndrome (ACS) and can be frequently found in culprit lesion segments. Trimethylamine N-oxide (TMAO) is reported to be involved in vascular calcification and plaque instability. This study investigated the relationship between plasma TMAO levels and calcified lesions in culprit lesion segments in STEMI patients. A prospective series of 179 patients with STEMI were enrolled, and calcified lesions from 127 patients were analyzed by OCT. The plasma TMAO levels were measured by using stable isotope dilution liquid chromatography tandem mass spectrometry. Patients were divided into two groups according to the median plasma TMAO level. The prevalence of intimal calcified lesions in the high TMAO group was significantly higher than that in the low TMAO group (90.6% vs. 57.1%, p<0.001; 84.4% vs 44.4%, p<0.001). After adjustment of traditional risk factors and medication history, patients with calcification in their culprit lesion segments had higher plasma TMAO levels than those without calcification. Moreover, plasma TMAO levels were significantly positively associated with the parameters of calcium burden, including maximal calcification arc (r=0.392, p<0.001), maximal calcification thickness (r=0.443, p<0.001) and calcified length (r=0.466, p<0.001). These results suggested that the level of TMAO is significantly correlated with the incidence of calcification in the culprit lesion segment, and the measurement of TMAO levels might improve clinical management in patients with heavy calcification.